2021
DOI: 10.1177/00027642211033296
|View full text |Cite
|
Sign up to set email alerts
|

The Past, Present, and Future of Brown’s Mandate: A View from North Carolina

Abstract: The unanimous 1954 Brown v. Board of Education opinion is one of the most consequential legal decisions of the 20th century. Even though it concerned government sanctioned racial segregation of public schools, many legal scholars, policy makers, and citizens see Brown’s impact going well beyond ordering the dismantling of de jure segregated public schools and instituting desegregated ones that would provide equitable high quality public education to all students irrespective of their race. Brown’s mandate over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Critical Race Theory challenges the colorblind ideal by arguing that colorblindness upholds racial inequality. In this vein, several education scholars have demonstrated that preventing racial segregation can require the active pursuit of racial integration (Ayscue et al, 2018; Mickelson et al, 2021; Roda & Wells, 2013). The findings of this paper echo this insight: assigning students to classrooms without regard to race and therefore without concern for racial integration has been a substantial source of racial segregation throughout Brazil’s public schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical Race Theory challenges the colorblind ideal by arguing that colorblindness upholds racial inequality. In this vein, several education scholars have demonstrated that preventing racial segregation can require the active pursuit of racial integration (Ayscue et al, 2018; Mickelson et al, 2021; Roda & Wells, 2013). The findings of this paper echo this insight: assigning students to classrooms without regard to race and therefore without concern for racial integration has been a substantial source of racial segregation throughout Brazil’s public schools.…”
Section: Discussionmentioning
confidence: 99%
“…While some literature on colorblind segregation focuses on how assigning students to classrooms or schools using ostensibly colorblind but race-correlated criteria promotes racial segregation (e.g., perceived ability in tracking, neighborhoods in school assignments), others have gone further, arguing that preventing racial segregation can require the active pursuit of racial integration. Scholars have demonstrated how the failure to promote racial integration facilitates the racial segregation of schools in the US in the contexts of laissez-faire school choice policies (Roda & Wells, 2013) and court decisions barring race-conscious remediation (Ayscue et al, 2018; Mickelson et al, 2021). That even truly random assignment can systemically produce racial segregation puts this insight into stark relief.…”
Section: Segregation By Chancementioning
confidence: 99%